Performance studies of wireless communication systems with selection diversity - Zhu, Yunfeng. (2009)
This report assesses the performance of selection diversity receiver in a slow, frequency-flat-fading channel in the presence of additive white Gaussian noise (AWGN). The signals are binary phase-shift keying (BPSK) or binary frequency-shift keying (BFSK) modulated. The fading channels include Rayleigh, Rician, and Nakagami-m fading channels. Simulations are done for the case where the fading variables for each channel are independent of each other. In that case, the analysis of the wireless system is fairly straightforward and theoretical expressions for the signal to noise ratio (SNR) and bit-error rate (BER) can be easily derived, which enables comparisons with simulated fading. In this project, equal-gain combining (EGC) and maximum-ratio combining (MRC) are also studied, and the simulation results are used to compare with selection diversity combining (SDC). Some conclusions can be drawn from this project. Signals have better performance when using BPSK modulation than using BFSK modulation. Rayleigh fading channel has the most fading effect compared with Rician and Nakagami-m fading channel. When diversity combining techniques are employed at the receiver, MRC is found to have the best performance, followed by EGC and SDC. It is also found that SDC and EGC have simpler receiver structure compared with MRC. SDC can be applied in both coherent and non-coherent detection.